Implementation of Argument Driven Inquiry Instructional Model to Improve Cognitive Learning Outcomes - Mazita, Aza; Siswanto Siswanto; Suwito Singgih; Nuryunita Dewantari; Djoko Sri Bimo (Indonesian Journal of Science and Education, 2024)
Cognitive learning outcomes are important basic skills that students must master. Science learning must be designed so that it can optimally provide students with the cognitive dimension. The importance of cognitive learning outcomes is in contrast to conditions in the field. Students' cognitive abilities in science learning are still low, especially at levels C2, C3 and C4. Observation results at Ihsanul Fikri Mungkid IT Middle School show that students' cognitive learning outcomes are still below the specified average, namely 78. The aim of this research is to analyze the effectiveness of learning using the Argument Driven Inquiry model in improving junior high school students' cognitive learning outcomes. This research uses a quantitative approach of the Quasi Experiment type, data analysis is carried out using the Mann Whitney test, N-Gain test, and effect size test. The research results show that the Argument Driven Inquiry (ADI) learning model is effective in improving the cognitive learning outcomes of junior high school students with an N-Gain of 0,7444, which is in the high category.